Ultrastructure of UVR‐B‐induced cataract and repair visualized with electron microscopy. (25th March 2014) - Meyer, Linda M.; Wegener, Alfred R.; Holz, Frank G.; Kronschläger, Martin; Bergmanson, Jan P.; Soderberg, Per G.
Abstract Purpose The aim of the study is to investigate and visualize the ultrastructure of cataract morphology and repair, after in vivo exposure to double threshold dose UVR‐B in the C57BL/6 mouse lens. Methods Twenty‐six‐week‐old C57BL/6 mice received in vivo double threshold dose (6.4 kJ/m2) UVR‐B for 15 min. The radiation output of the UVR‐source had λMAX at 302.6 nm. After a latency period of 1, 2, 4 and 8 days following UVR‐B exposure, the induced cataract was visualized with electron microscopy techniques. Induced, cataract was quantified as forward lens light scattering. Damage to the lens epithelium and the anterior cortex was investigated with light microscopy in toluidine blue‐stained semi‐thin sections, transmission electron microscopy (TEM), scanning electron microscopy (SEM) and dark field illumination photography. Results UVR‐B‐exposed lenses developed anterior subcapsular and/or cortical and nuclear cataract after 1 day. Lens light scattering peaked 2 days after exposure. Lens epithelial cell damage was seen in TEM as apoptotic cells, apoptotic bodies, nuclear chromatin condensation, and swollen and disrupted anterior cortex fibres throughout the sections of the whole anterior lens surface. These morphologic changes were also visualized with SEM. Within 8 days, anterior subcapsular cataract was repaired towards the anterior sutures. Conclusion UVR‐B exposure of double cataract threshold dose induces a subtotal loss of epithelial cells across the whole anterior surface of the lens. This damage to the epithelium is repaired by epithelial cell movement from the equator towards the lens sutures, thus in retrograde direction to regular epithelial cell differentiation.